ARTIFICIAL INTELLIGENCE IN DIGITAL GAMES - Gobete Filho, Alexandre Roberto; Lucca Filho, João de (Revista Interface Tecnológica, 2022)
This work approaches the use of artificial intelligence (AI) in digital games. In this way, the evolution of AI was introduced since the 1950s, punctuating two lines of research: Connectionist AI focused on emerging intelligence from the physiology of the human brain through neural networks; and Symbolic AI driven by computer systems to describe intelligent behavior through mathematics. The work also presents the main advances that occurred during the development of AI, as well as the development and use of AI in the digital games industry. Finally, the applications of AI with the real world and the evolution of the digital games industry are analyzed.